Analysis of the mechanical properties of concretes with partial and total replacement of natural coarse aggregates by recycled aggregates - Fonseca Junior, Gerardo Alves da; Leite, Juliana Corrêa Trindade; Mendez, Gabriel de Pinna; Haddad, Assed Naked; Silva, José Augusto Ferreira da; Costa, Bruno Barzellay Ferreira da (Brazilian Journal of Production Engineering, 2025)
Given the increase in global concrete consumption, environmental impacts have also intensified, requiring the construction sector to develop concrete production in line with the Sustainable Development Goals (SDGs). In this context, the use of Construction and Demolition Waste (CDW) as a replacement for natural aggregates emerges as an alternative. Therefore, the objective of this study was to analyze the compressive and tensile strength of concrete produced with recycled aggregate in comparison to reference concrete, through an experimental program using recycled concrete coarse aggregates with maximum diameters of 9.5 mm and 19 mm. For each granulometry, concrete mixtures were produced with natural aggregate replacement ratios of 0%, 30%, 50%, and 100%. Strength tests revealed that the target compressive strength of 25 MPa was achieved by all mixtures, while tensile strength reached between 8% and 12% of compressive test values. The ANOVA statistical method verified that all studied mixtures presented statistically equal mean strengths at 28 days. These results demonstrate that recycled aggregate concrete can be a promising material for the construction sector, while also contributing to SDG 12: Responsible Consumption and Production.